Atrial fibrillation and flutter and ocular diseases: the Ural eye and medical study and the Ural very old study - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Rakhimova, Ellina M.; Panda-Jonas, Songhomitra; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Rusakova, Iulia A.; Jonas, Jost B. (Acta ophthalmologica, 2024)
Purpose To assess associations between atrial fibrillation/atrial flutter (AF) and ocular parameters and diseases. Methods The population-based Ural Eye and Medical Study (UEMS) and the Ural Very Old Study (UVOS) included 4894 individuals (age: 40+ years) and 835 individuals (age: 85+ years), respectively. Results In the UEMS, AF prevalence (80/4894; 1.6%; 95% CI: 1.3, 2.0) increased from 1/1029 (0.1%) in the age group of 40 to <50 years to 29/619 (4.7%) and 12/159 (7.5%) in the age groups of 70 to <80 years and 80+ years, respectively. Higher AF prevalence correlated with older age (OR: 1.08; 95% CI: 1.04, 1.12; p < 0.001), urban region of habitation (OR: 1.08; 95% CI: 1.04, 1.12; p < 0.001), higher prevalence of cardiovascular disease/stroke (OR: 2.50; 95% CI: 1.32, 4.72; p < 0.001) and lower prevalence of neck pain (OR: 0.35; 95% CI: 0.14, 0.85; p = 0.02), higher serum concentration of bilirubin (OR: 1.03; 95% CI: 1.02, 1.05; p < 0.001) and lower prothrombin index (OR: 0.96; 95% CI: 0.93, 0.99; p = 0.003), higher stage of arterial hypertension (OR: 1.52; 95% CI: 1.01, 2.28; p = 0.04) and higher ankle-brachial index (OR: 22.1; 95% CI: 4.45, 1.10; p < 0.001). In that model, AF prevalence was not associated with ocular parameters such as intraocular pressure (p = 0.52), retinal nerve fibre layer thickness (p = 0.70), refractive error (p = 0.13), axial length (p = 0.14), nuclear cataract degree (p = 0.50) and prevalence (p = 0.40), cortical cataract degree (p = 0.43) and presence (p = 0.17), lens pseudoexfoliation (p = 0.58), status after cataract surgery (p = 0.38), age-related macular degeneration prevalence (p = 0.63), open-angle glaucoma presence (p = 0.90) and stage (p = 0.55), angle-closure glaucoma prevalence (p = 0.99) and stage (p = 0.99), diabetic retinopathy prevalence presence (p = 0.37) and stage (p = 0.32), and myopic macular degeneration (p = 0.98). In the UVOS, similar results were obtained. Conclusions In these multi-ethnic populations from Russia, AF prevalence was not associated with any major ocular disease and may not play a major role in the pathogenesis of these disorders.
Erstmals veröffentlicht: 01. Juni 2024
Gesehen am 19.11.2024